Infinity son - Silvera, Adam, 1990- (HarperTeen, an imprint of HarperCollinsPublishers, 2020)
"In a world where some people are born with powers and some people take them, brothers Emil and Brighton Rey get swept up in a supernatural turf war generations in the making"--